Exploring Factors Influencing MOOCs Usage Behavior and Technology Acceptance in Higher Education: An Analysis Using the UTAUT Model - Kiki Awaliyah; Arum Putri Rahayu; Putri Olivia; Muh Ma’ruf Asya Perdana (Academic Bright Collaboration, 2025)
Indonesian higher education still faces uneven adoption and low completion that may be driven by students’ technology acceptance and available support. This study investigated key determinants of Universitas Negeri Makassar students’ MOOCs acceptance and usage behavior using the Unified Theory of Acceptance and Use of Technology (UTAUT). A descriptive quantitative, cross-sectional survey was administered via Google Forms to 33 undergraduate students. The instrument comprised 34 Likert-scale items (1–5) measuring eight UTAUT-related dimensions: performance expectancy, effort expectancy, social influence, facilitating conditions, computer self-efficacy, attitude toward technology, behavioral intention, and actual use; data were analyzed using descriptive statistics. Overall perceptions were fairly positive, with most indicator means in the moderate-to-agree range. Performance expectancy (e.g., perceived usefulness and learning improvement) was moderate (means ≈3.52–3.55) and effort expectancy suggested MOOCs were relatively easy to learn (means ≈3.48–3.51). Social influence was weaker (means ≈3.24–3.30), while facilitating conditions were strongest, including system compatibility (mean ≈3.58). Behavioral intention was moderate (e.g., plan to use MOOCs; mean ≈3.55), yet actual use was comparatively lower (means ≈3.21–3.33), indicating an intention–use gap. Strengthening institutional support (infrastructure, guidance, integration with campus systems) and targeted interventions to convert intention into sustained participation may improve MOOCs uptake and completion; overall, the findings support UTAUT’s usefulness for diagnosing adoption barriers in Indonesian university contexts.